Parliamentary behaviour of the members of opposition political parties in Malaysia - Omar, Muhamad Fuzi (IIUM Press, 2008)
In a hegemonic consociational system practised in Malaysia, the Opposition can hardly play a dominant role in making democracy work. Nevertheless, a content analysis of the debates in the House of Representatives from 1982 to 2003 show that the opposition members have contributed to the process of check and balance in the government by asking questions to relevant ministries and by initiating adjournment motions. In the process, they not merely attacked the government for their failure but also suggested alternative policies some of which were implemented by the ruling coalition